Correction: Kubicki, M.; Park, H. Metal-Plated Connections in Sustainable Lightweight Construction: A Weak Link in Fire Conditions? Sustainability 2024, 16, 6923 - Kubicki, Michael; Park, Haejun (Sustainability, 2024)
The authors would like to make the following corrections to the published paper [...]